Four years after the implementation of antimicrobial stewardship program in Jordan: evaluation of program’s core elements - Hassan, Samar Khaled; Dahmash, Eman Zmaily; Madi, Thaira; Tarawneh, Omar; Jomhawi, Tuqa; Alkhob, Worood; Ghanem, Rola; Halasa, Zina (Frontiers in Public Health, 2023)
OBJECTIVES: To combat antimicrobial resistance, the World Health Organization (WHO) urged healthcare organizations in Low- and Middle-Income Countries (LMICs) to implement the core elements of the antimicrobial stewardship (AMS) programs. In response, Jordan took action and developed a national antimicrobial resistance action plan (NAP) in 2017 and commenced the AMS program in all healthcare facilities. It is paramount to evaluate the AMS programs' efforts and understand the challenges of implementing a sustainable and effective program in Low-Middle Income Country (LMIC) contexts. Therefore, the aim of this study was to appraise the compliance of public hospitals in Jordan to the WHO core elements of effective AMS programs after four years of commencement. METHODS: A cross-sectional study in public hospitals in Jordan, using the WHO AMS program core elements for LMICs was carried out. The questionnaire comprised 30 questions that covered the program's six core elements: leadership commitment, accountability and responsibility, AMS actions, education and training, monitoring, and evaluation, and reporting and feedback. A five-point Likert scale was employed for each question. RESULTS: A total of 27 public hospitals participated, with a response rate of 84.4%. Adherence to core elements ranged from (53%) in the leadership commitment domain to (72%) for AMS procedure application (actions). Based on the mean score, there was no significant difference between hospitals according to location, size, and speciality. The most neglected core elements that emerged as top priority areas were the provision of financial support, collaboration, access, as well as monitoring and evaluation. CONCLUSIONS: The current results revealed significant shortcomings in the AMS program in public hospitals despite four years of implementation and policy support. Most of the core elements of the AMS program were below average, which requires hospital leadership commitment, and multifaceted collaborative actions from the concerned stakeholders in Jordan.